Impact of Covid-19 on Islamic Phylantrophic Behavior of Lecturers - Pradesyah, Riyan; Bara, Al (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The spread of the Covid-19 virus in Indonesia has an impact on all sectors, and one sector that is currently experiencing a significant impact is the economic sector. Universitas Muhammadiyah Sumatera Utara (UMSU), is an A-accredited private campus, which now still provides fixed salaries and incentives, there is no reduction even though the spread of covid has an impact on all sectors. Many private campuses in Medan City have reduced the salaries of their employees, and even removed some incentives to reduce the budget used, but not for UMSU which still provides obligations and other incentives. In this case, it means that the welfare of Muhammadiyah University employees is still being considered by the leadership stakeholders, but from the observations made, researchers see a decrease in infaq obtained by LAZISMU Medan City. Therefore, the researchers want to see the relationship between the spread of the Covid-19 virus and the philanthropy embraced by employees of UMSU. The Islamic philanthropy is in form of infaq and alms. The research is descriptive qualitative research, which the results obtained will be described or narrated in accordance with the rules of qualitative research. From the results obtained, that there was a shift in Islamic philanthropy carried out by UMSU employees, this happened only a few months after the outbreak of Covid-19 which spread in the city of Medan.